EVALUASI IMPLEMENTASI STANDAR PENILAIAN OLEH GURU MATEMATIKA DI SMA NEGERI 3 WATAMPONE KABUPATEN BONE - Muh. Bachtiar Aziz (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study aims to describe the assesment planning, overview of assesment implementation, and reporting result/impact of the assesment at SMA 3 Watampone, based on the aspects of antecedents, transactions, and outcomes. This research is an evaluation study which is used by mathematical teachers at SMAN 3 Watampone. Data were analyzed using descriptive data analysis in the form of frequency distribution and percentages. Subjects in this study were the principal, vice principal, math teachers, and students. Data were collected by employing questionnare, interview, and documentation. The result shows that evaluation results of the implementation of assesment standard by mathmatics teacher at SMAN 3 Watampone based on recapitulation aspects of planning (antecedents), implementation (transactions), and result/impacts (outcomes) are in the good category. It is harmonized by (1) Planning Assesment, the school provide a syllabus and assesment guidelines that serve as a giude for teachers. (2) The implementation of assesment, assesment activities such as the provision of assignments and quizzes are in conformity with the plan thats is prepared at the beginning of learning activities. (3) Results/impact, teacher processing, scoring, input the score in the valuation list, then report the result to the class teacher, school principal, and invite the parents/guardians of the students. Keywords: evaluation program, assessment standard, mathematics